G. O. D. : givers of death [videorecording (DVD)] - Henderson, Addison; Henderson, Addison; Alfieri, J. J.; Lombardi, Louis, 1968-; Sterritt, Jonathan (Buffalo 8, 2022)
An incurable virus has wiped out one third of the world's population. Many infected commit suicide to end their agony. Those who cannot bring themselves to end their own lives hire professionals. This is the journey of a hitman's quest for peace as he navigates through a city on the brink of collapse, while on the run from a detective seeking revenge.